Effect of Oxymatrine Combined with Low Dose 5-FU on Lymphatic Vessel and Microvascular Endothelial Cell Growth of Gastric Cancer in a Severe Combined Immunodeficient Mouse Orthotopic Implantation Model - J-S. Zhu (European Journal of Inflammation, 2011)
In this study, we explored the effect of Oxymatrine combined with low dose 5-Fu on lymphatic vessel and vascular endothelial growth factor of orthotopic implantated gastric cancer in severe combined immunodeficient (SCID) nude mice. Human gastric cancer cell line SGC-7901 was orthotopically implanted into the gastric tract of nude mice. Nude mice were treated with normal saline (control group), low dose 5-Fu, oxymatrine, oxymatrine combined with low dose 5-Fu using intraperitoneal injection. The expression of LVD, VEGF-C, VEGF-D, VEGF-R-3 and their Ct were analyzed in a severe combined immunodeficient mouse orthotopic implantatation gastric cancer model. We found that oxymatrine combined with low dose 5-Fu could decrease LVD and inhibit VEGF expression by a synergistic effect in SCID nude mouse orthotopic implantatation gastric cancer model.